Covid-19 Pandemic as Force Majeure Unable to Fulfill Obligation in Financing Agreement - Dewantoro Dewantoro; Achmad Busro; Ery Agus Priyono (Universitas Negeri Semarang, 2023)
The Covid-19 health pandemic as an example of a form of force majeure can affect how risk is assigned to the parties bound by the agreement regarding the inability to pay in a financing agreement caused by force majeure. The research was conducted using normative legal research methods by examining literature (secondary data). From the results of the research, it can be concluded that a dispute resolution institution or court in dealing with disputes regarding the termination of a financing agreement caused by the debtor’s inability to pay due to the impact of the Covid-19 health pandemic must be able to assess the good faith of the debtor in implementing the financing agreement so that it can present the value of justice in the resolution of related disputes financing agreement. The role of the court is a sign of the presence of the state in presenting the value of social justice for the Indonesian people.